Inklusivitas di Tempat Kerja: Upaya Memenuhi Hak dan Fasilitas bagi Penyandang Disabilitas - Nashiha, Adhinun; Alqadri, Ahmad Aqil; Utami, Yeski Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Policy changes between Law No. 13 of 2003 and the Work Creation Law have impacted the difficulty faced by people with disabilities in obtaining jobs, exacerbated by the lack of public awareness about this group. This study aims to provide further insights into the laws governing people with disabilities and clarify the categories of individuals included within this group. The methodology employed is a literature review, defined as a summary derived from reading sources relevant to the research topic. A notable change is the shift in terminology from "persons with disabilities" to "persons with disabilities," which is considered more polite and respectful. However, the laws and government regulations lack clear provisions on quotas for employing people with disabilities. Establishing such quotas is essential to enhance welfare and ensure equal opportunities for all members of society. People with disabilities are categorized into physical, sensory, intellectual, and mental groups.